Early Experience with Pancreatic, Periampullary malignancies: Case Reviews, Management Guidelines and Discussion - Rawal, S; Giri, N; Thapa, D; Lama, D (Medical Journal of Shree Birendra Hospital, 2006)
Early Experience with Pancreatic, Periampullary malignancies: Case Reviews, Management Guidelines and Discussion